Application of Smart Waste Management Strategies for Sustainable Waste Management - G, Senthilkumar (International Research Journal of Multidisciplinary Technovation, 2019)
India is moving towards development of smart cities which requires a marked improvement in Municipal Solid Waste Management (MSWM) to provide a clean and aesthetically appealing environment specifically in urban agglomerations. Presently India is producing around 65 million tones of municipal solid waste annually and 80% of which is dumped simply on the open ground. Even after the Solid waste management rules 2016 comes into effect there is no marked improvement in the waste management. The use of technologies like Internet of Things (IoT) and adopting a policy of smart waste – smart resources it is possible to create more robust Sustainable solid waste management systems. IoT is a concept that connects numerous and various physical objects to the internet with the help of sensors and other wireless technologies, conceptually the process of connecting different types of devices extracting the data from them to perform an action in the context of data read. With Swatch Bharath, Clean India mission and the development of Smart cities projects the government of India is offering and encouraging a phenomenal change in waste management policies and action plans with an objective to make the waste management technically feasible, environmentally and financially sustainable. In the present study an assessment of existing waste management scenario was carried out for the semi urban location, Annamalai Nagar Special town Panchayat of Cuddalore District in Tamilnadu state. IoT based waste management has been proposed, the ill effects of the present waste management practices and likely benefits of the application of technology enhanced IoT based waste management have been compared for the real time waste management system.